An Innovative study on Rural Planning with Cultural Integration as a Tourism Development Model: A Case of Chahaer Youyii Qianqi - Liang, Yan (Pacific International Journal, 2023)
In the 2017 report of the 19th National Congress, it was pointed out that the issue of agriculture, rural areas, and farmers is a fundamental issue related to the people’s livelihood of the country. The solution of the "three rural issues" must always be the top priority of the work of the whole Party and the implementation of the rural revitalization strategy. In the context of the rural revitalization strategy, this paper analyzes the current situation of Chahaer Youyii Qianqi, Inner Mongolia, and the drawbacks of the traditional tourism model. The study finds that the traditional model of tourism is a single "show and view" commercial complex, which rarely reflects the original Mongolian ethnic identity, spiritual connotations and sustainable development strategies. The analysis is intended to provide an overall plan for the village and to create a new type of village with sustainable development in terms of housing, tourism, agriculture, and pastoralism. The aim is to create an experiential tourism model based on the integration of multiple ethnic groups, the restoration of the original Mongolian form of habitation through a combination of clustered units, the development of cultural integration, the principle of sustainable development, the diversification of tourism forms, the diversification of industrial structures, and the construction of a complete infrastructure.